2023
DOI: 10.3390/life13020469
|View full text |Cite
|
Sign up to set email alerts
|

Natural Co-Exposure to Borrelia burgdorferi s.l. and Anaplasma phagocytophilum: Unraveling the Hematological Profile in Sheep

Abstract: The occurrence of co-infected hosts and questing ticks with more than one tick-borne pathogen—as in the case of Anaplasma phagocytophilum and Borrelia burgdorferi sensu lato—is expected in endemic regions. Their synergy—in terms of pathogenesis and disease severity—has been suggested previously in humans. Limited data exist on the clinicopathological alterations in co-infected sheep. In this study, we investigated the impact of A. phagocytophilum and B. burgdorferi s.l. seropositivity, alone and in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…The studies conducted up to now showed a low seroprevalence of 3.3% in humans [ 73 ] and 0.1–2.2% in dogs [ 74 , 75 ]. Recently, a study showed that sheep are also exposed to B. burgdorferi in Greece and provided evidence of co-exposure with A. phagocytophilum [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted up to now showed a low seroprevalence of 3.3% in humans [ 73 ] and 0.1–2.2% in dogs [ 74 , 75 ]. Recently, a study showed that sheep are also exposed to B. burgdorferi in Greece and provided evidence of co-exposure with A. phagocytophilum [ 76 ].…”
Section: Discussionmentioning
confidence: 99%